Justification and choice of hardware for automatic control system by technical means at the garage consumer cooperative - Krasnykh V. Y., Tumor S. V. (Interactive science, 2017)
the article describes the main system requirements of software of finished products for implementation of an automatic control system by technical means at the garage consumer cooperative.
Keywords: программное обеспечение; software; централизованная структура; гаражно-потребительский кооператив; centralized structure; garage consumer cooperative